Analisis Jumlah Lilitan dan Variasi Material Inti Besi Stator Rotor Terhadap Efisiensi Permanent Magnet Synchronous Generator 24 Slot 16 Pole Fluks Radial - Hidayah, Fikri; Gusnita, Novi (Universitas Al Azhar Indonesia, 2023)
Effort to replace increasingly limited fossil energy sources, new renewable energy (EBT) can be the right solution. This type of energy comes from natural resources that can be renewed continuously, such as wind energy. Permanent Magnet Synchronous Generator (PMSG) technology can be used optimally in wind turbines. However, research on the efficiency of this technology is still not optimal in terms of reducing energy consumption, power losses and operational costs. Therefore efforts are needed to increase generator efficiency. The generator is the main component of converting wind energy into electrical energy. The research was conducted on a 24 slot 16 pole permanent magnet synchronous generator type using the Finite Element Method (FEM) with 3 variations of the number of turns of 35, 50, 65 and variations of the stator rotor iron core material: TR 52: USS Transformer, Remko Soft: Pure, M1000-100A Silicon Steel. This research resulted in the highest current value of 9.92 Amperes, the highest voltage value was 99.2 volts, the value of the input power was 1199.2 Watts and the output power was 1014 Watts on the number of turns of 65 coils and Remko material: soft pure and for efficiency the best is obtained at a value of 87.20% on the number of turns of 50 turns and Remko material: Soft Pure.Keywords – PLTB, Generator, Coil, Iron Core, Permeability Magnet.